Synthesis and performance evaluation of a nanocomposite comprising polyacrylamide hydrogel reinforced with pectin and titanium dioxide for the delivery of curcumin - Fatemeh Mohajjel Jafari; Mehrab Pourmadadi; Majid Abdouss (Carbohydrate Polymer Technologies and Applications)
Due to the increase in cancer and the necessity for effective therapies with minimum side effects, researchers throughout the world are investigating novel methods for delivering drugs to deal with this deadly disease. Nanocarriers lower side effects and improve anticancer drug efficacy by targeting and controlling drug release. The intended nanocarrier in this study includes polyacrylamide hydrogel, pectin, and titanium dioxide nanoparticles to release curcumin. This pH-sensitive nanocarrier was synthesized using a water/oil/water double emulsion method. FT-IR, XRD, and FE-SEM analyses were performed to investigate the chemical interactions, crystallinity, and morphology of the nanocarrier. The average particle size and PDI parameters were obtained as 171.25 nm and 0.34, respectively. The zeta potential value was also calculated to be +41.76 mV. LE and EE values were calculated using a UV–vis spectrophotometer device at 425 nm as 48 % and 90 %, respectively, and in comparison to previous studies, the PAM/Pec/TiO2@Cur nanocarrier has greater values. The pH responsively of the nanocarrier was confirmed by evaluating the release of Cur by the dialysis technique at both acidic and neutral pH. To further understand the drug release mechanism, the kinetics of release were studied at pH 5.4 and 7.4. Based on MTT assay results, the survival percentage of A549 cells against free Cur and nanocarrier was 65 % and 45 %, respectively. Therefore, the analysis of the data and the results obtained at various stages show that the nanocarrier synthesized in this study has the potential to be an excellent cancer therapy option.